Cognitive Dysfunctions in Glaucoma: An Overview of Morpho-Functional Mechanisms and the Impact on Higher-Order Visual Function - Arrigo, Alessandro; Aragona, Emanuela; Saladino, Andrea; Arrigo, Davide; Fantaguzzi, Federico; Battaglia Parodi, Maurizio; Bandello, Francesco (Frontiers in Aging Neuroscience, 2021)
Background: Glaucoma is a chronic, vision-threatening disease, and a major cause of legal blindness. The current view is no longer limited to the progressive optic nerve injury, since growing evidence strongly support the interpretation of glaucoma as a complex neurodegenerative disease. However, the precise pathogenic mechanisms leading to the onset and progression of central nervous system impairment, and the functional consequences of this damage, are still partially understood. The main aim of this review is to provide a complete and updated overview of the current knowledge regarding the central nervous system involvement in glaucoma, and the possible therapeutic perspectives. Methods: We made a careful survey of the current literature reporting all the relevant findings related to the cognitive dysfunctions occurring in glaucoma, with specific remarks dedicated on the higher-order visual function impairment and the possible employment of neuroprotective agents. Results: The current literature strongly support the interpretation of glaucoma as a multifaceted chronic neurodegenerative disease, widely affecting the central nervous system. The cognitive impairment may vary in terms of higher-order functions involvement and in the severity of the degeneration. Although several neuroprotective agents are currently available, the development of new molecules represents a major topic of investigation for future clinical trials. Conclusions: Glaucoma earned the right to be fully considered a neurodegenerative disease. Glaucomatous patients may experience a heterogeneous set of visual and cognitive symptoms, progressively deteriorating the quality of life. Neuroprotection is nowadays a necessary therapeutic goal and a future promising way to preserve visual and cognitive functions, thus improving patients’ quality of life.